Lino block printmaking in visual arts education for form 1 transition students: A project-based approach to cultural and environmental literacy - Bileron Buruntong; Harozila Ramli; Tajul Shuhaizam Said; Salbiah Kindoyop; Musnin Misdih; Nor Aznoni Mohamed; Natilie Kuintin (International Journal Of Modern Education (IJMOE), 2025)
This study explores the effectiveness of Lino Block Printmaking as an innovative pedagogical approach in visual arts education for form 1 Transition students. By integrating themes of flora and fauna, this technique promotes interdisciplinary learning, encouraging students to develop technical proficiency, creative expression, and cultural and environmental awareness. Through a qualitative case study approach, data were collected via classroom observations, student artwork analysis, and semi-structured interviews involving 42 form 1 Transition students. Findings reveal significant improvements in artistic skills and technical mastery, particularly in carving techniques, ink application, and manipulating positive and negative space. Students demonstrated enhanced control over line thickness and motif detailing, resulting in visually appealing and sophisticated prints. Furthermore, the project-based learning framework effectively reinforced students’ understanding of essential visual arts concepts, including balance, contrast, repetition, and composition. Additionally, the thematic exploration of flora and fauna motifs fostered a deeper appreciation of local biodiversity and cultural heritage. The incorporation of sustainable art practices, such as using eco-friendly materials, heightened students’ awareness of ethical and responsible creative practices. This interdisciplinary approach not only promoted artistic growth but also contributed to developing critical thinking, problem-solving, and reflective skills. The study concludes that Lino Block Printmaking serves as a valuable educational tool for enhancing students’ artistic and conceptual competencies while promoting cultural and environmental literacy. Recommendations include integrating digital tools, encouraging eco-friendly practices, and organizing student exhibitions to maximize learning outcomes.